LC3B, a Protein That Serves as an Autophagic Marker, Modulates Angiotensin II-induced Myocardial Hypertrophy. Issue 6 (December 2015) - Huang, Jionghua; Pan, Wei; Ou, Dejin; Dai, Wenjun; Lin, Yuhui; Chen, Yongquan; Chen, Ximing
Abstract : Abstract: LC3B is a marker of autophagic activity, and growing evidence supports its importance in myocardial hypertrophy. Thus, regulating LC3B expression may provide an important avenue to inhibit autophagy and protect against or inhibit pathological myocardial hypertrophy. To address this question, we investigated the effects of altering LC3B mRNA expression and autophagic activity in the setting of cardiomyocyte hypertrophy. In an in vitro angiotensin II (Ang II)-induced cardiomyocyte hypertrophy model, LC3B mRNA and protein expression was increased and there was activation of cardiomyocyte autophagy, which was assessed by transmission electron microscopy and flow cytometry. LC3B cDNA transfection also resulted in an upregulation of autophagic activity, whereas downregulation of autophagic activity was observed with knockdown of LC3B expression. Induction of LC3B expression was shown to further exacerbate Ang II-stimulated cardiomyocyte hypertrophy, whereas inhibition of LC3B expression inhibited the Ang II-stimulated cardiomyocyte hypertrophy (as assessed through cardiomyocyte morphology and expression of ANP and β-MHC). This study demonstrated that LC3B modulates the Ang II-induced cardiomyocyte hypertrophy in cultured neonatal rat ventricular cardiomyocytes.